Antibiotic Prophylaxis in the Management of Open Fractures: A Systematic Survey of Current Practice and Recommendations. Issue 2 (February 2019) - Chang, Yaping; Bhandari, Mohit; Zhu, Kan Lun; Mirza, Reza Donald; Ren, Melody; Kennedy, Sean Alexander; Negm, Ahmed; Bhatnagar, Neera; Naji, Faysal N.; Milovanovic, Lazar; Fei, Yutong; Agarwal, Arnav; et al.
Abstract : Background: Evidence with regard to antibiotic prophylaxis for patients with open fractures of the extremities is limited. We therefore conducted a systematic survey addressing current practice and recommendations. Methods: We included publications from January 2007 to June 2017. We searched Embase, MEDLINE, CINAHL, the Cochrane Central Registry of Controlled Trials (CENTRAL), and the Cochrane Database of Systematic Reviews for clinical studies and surveys of surgeons; WorldCat for textbooks; and web sites for guidelines and institutional protocols. Results: We identified 223 eligible publications that reported 100 clinical practice patterns and 276 recommendations with regard to systemic antibiotic administration, and 3 recommendations regarding local antibiotic administration alone. Most publications of clinical practice patterns used regimens with both gram-positive and gram-negative coverage and continued the administration for 2 to 3 days. Most publications recommended prophylactic systemic antibiotics. Most recommendations suggested gram-positive coverage for less severe injuries and administration duration of 3 days or less. For more severe injuries, most recommendations suggested broad antimicrobial coverage continued for 2 to 3 days. Most publications reported intravenous administration of antibiotics immediately. Conclusions: Current practice and recommendations strongly support early systemic antibiotic prophylaxis for patients with open fractures of the extremities. Differences in antibiotic regimens, doses, and durations of administration remain in both practice and recommendations. Consensus with regard to optimal practice will likely require well-designed randomized controlled trials. Clinical Relevance: The current survey of literature systematically provides surgeons' practice and the available expert recommendations from 2007 to 2017 on the use of prophylactic antibiotics in the management of open fractures of extremities.